Creating A Prima Service In Building Customer Satisfaction - Rudiatsyah Rudiatsyah (Jurnal Akuntansi dan Pajak, 2013)
The purpose of this study is to know the purpose of value and customer satisfaction, to know how the company provides value and high satisfaction to customers, to know how companies attract and retain customers, to determine the determination of customer profitability, and to determine the application of total quality marketing in the company. The research method used in this study is a literature review obtained from journals, books, and other relevant sources. Customer satisfaction and loyalty is the most important thing in running a business / business. When running the business the company demanded the power of service provided to the customers. Therefore, the quality of service should receive serious attention from management. Attention to the consumer becomes important, with the effort to listen to the voice of the consumer and then help him to formulate his needs.